Biblioteczne szkolenia i jak je znaleźć. Analiza wybranych elementów witryn internetowych polskich bibliotek publicznych uczelni akademickich = Library training sessions and how to find them. An analysis of selected elements of websites of the Polish public libraries of university colleges - Banaszewski, Kamil; Bartosiak, Katarzyna (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
Library training sessions, as well as broader didactic activities on the part of libraries, are becoming more and more important, and are having a positive impact on the image of libraries themselves. Additionally, if offered in an attractive manner through a website that respects the rules of web-design, they can contribute significantly to the promotion of universities themselves. It is important, therefore, whether and how this information is placed on libraries? websites. The article presents the results of research into the locating of information about library training sessions on the websites of libraries of Polish state universities, including such indicators as the availability of training information on the main page of the library, their location (home page or subpages), the number of places on the website in which such information is found by the user, or the presence of such information in library news.
Keywords: Szkolenia biblioteczne; biblioteki uniwersyteckie; strony internetowe; promocja bibliotek; Dydaktyka biblioteczna; Library training sessions; University libraries; websites; Library promotion; Library instruction/didactics